Conhecimento de Deus pela experiência: uma hermenêutica de Jó 42, 1-6. - Batista, Rodrigo Rios (2023)
The textual corpus of the Holy Scriptures becomes a documental source of knowledge of God, the result of an oral tradition transmitted through several generations. In it, it is possible to observe in the facts that involve the chosen people, the progressive knowledge of the divinity in each event that follows the composition of its history. Two spheres of cultural experiences were the basis for the construction of this knowledge: the real and the domestic. The first is subdivided into prophetic and omniscient narrative, and the second takes place in proverbial style. The book of Job has at its core divine knowledge from the perspective of the Theology of Retribution. To understand it, it is necessary to delve into the concepts of blessing, curse and the meaning of the distribution of divine justice to maintain a cosmic and social order. The main character problematizes this doctrine with her statements. The work does not propose an elimination of suffering, but a theological interpretation of it. This pervades the way the image of God is conceived, which is even different in the two blocks of the book, composed in prose and poetry. This dissertation focuses on this second part in which suffering is questioned as a direct result of sins, thus allowing a way of understanding through gratuitousness in the relations between God and human beings. Finally, a hermeneutics of Job 42, 1-6 is proposed. These verses show Job's recognition of his limitations of knowledge. He claims that he only knew God by “ears” and after the suffering he experienced, he was able to see Him in a different way. From the text in Hebrew, it is shown that the source of science became contact through vision, as a revelation, revealing the progress that took place in Job's cognitive process. The character then assumes a new behavior, with penitential practices known in the Bible. The assent to faith is given through gratuity, showing that the experience of undeserved suffering was the path to a different divine knowledge from what had been transmitted by traditions.